Intestinal permeability studies for piperaquine from dihydroartemisinin—piperaquine antimalarial product in the presence of lamivudine - Sunday O. Awofisayo, Ayodeji A. Agboke, Ekpedeme N. Essien, Chioma N. Igwe (Journal of Applied Pharmaceutical Science, 2018)
The study assessed the intestinal permeability of piperaquine (PQ) from dihydroartemisinin–piperaquine (DP) antimalarial in the presence of lamivudine (LMV). Excised tissues (duodenum and ileum) from New Zealand male albino rabbits (n = 2) were loaded with a suspension of DP equivalent to PQ (100 mg/ml) and LMV (100 mg/ml) and submerged in Tyrode solution (TS). DP suspension was similarly loaded as control. Sampling (5 ml) of TS was done post immersion of tissues and analyzed for PQ permeation using the high pressure liquid chromatographic system. LMV caused a significant increase in PQ permeation across the intestinal membranes. The rate constant (Ka) appearance in organ bath was (0.2457 ± 0.0040 hour−1 vs. 0.0367 ± 0.0008 hour−1, p = 0.010) for duodenum and (0.2428 ± 0.0006 hour−1 vs. 0.0327 ± 0.0021 hour−1, p = 0.008) for ileum. The Ka disappearance of PQ was (1.0121 ± 0.0013 hour−1 vs. 0.7600 ± 0.0008 hour−1, p = 0.001) from duodenum and (1.0092 ± 0.0003 hour−1 vs. 0.7340 ± 0.0072 hour−1, p = 0.017) from ileum. Area under the curve at 6 hours was (1.2868 ± 0.6725 μg.ml hour−1 vs. 3.3975 ± 0.3638 μg.ml hour−1, p = 0.034) for duodenum and (0.7425 ± 0.0089 μg.ml hour−1 vs. 5.6603 ± 0.1073 μg.ml hour−1, p = 0.013) for ileum. Co-loading of LMV with DP ex vivo caused significant uptake from the lumen but significant reduction in PQ permeation across the intestinal regions into the organ bath. This may be of biopharmaceutical implication requiring dosage adjustments.
Keywords: Dihydroartemisinin– piperaquine, piperaquine, lamivudine, permeability, intestinal membrane.